"Legal Method, Legal System and Legal Research" - "kumar, Ashok" (New Delhi, 2014)
This Book is written to serve the needs of the Students of Law of the First Year & it contains the most aspects of the legal systems & Leagal research. The Legal Method is an important subject in study of Law & considered as foundation of the subject. The book is split into eleventh Chapters. The Chapter one deals with the general Methods & Legal Method of the Study. The Chapter two is concerned to Jurisprudence & its Schools. The Chapter Third deals with the nature & Function of Law. The Chapter Fourth deals with sources of Law. Fifth discusses the Crime & Civil wrong. Sixth concerned to Constitution as basic Law. Seventh deals with Seperation of Power. Chapter Eightth is devoted to Legal System. Nineth analyses to Moot Court, Mock Trial & Study Method.The chapter Tenth discusses about the Legal Profession & Professional Ethics. The Chapter Eleventh deals with the Legal Research & Legal Writing. The Language of the Book is Easy & understandable to Students..
Keywords: "Law research, Law methodology"